1999
DOI: 10.1128/mcb.19.11.7712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Vacuolar Pyrophosphatase in Trypanosoma brucei and Its Localization to Acidocalcisomes

Abstract: Inorganic pyrophosphate promoted the acidification of an intracellular compartment in permeabilized procyclic trypomastigotes of Trypanosoma brucei, as measured by acridine orange uptake. The proton gradient generated by pyrophosphate was collapsed by addition of nigericin or NH 4 Cl. Pyrophosphate-driven proton translocation was stimulated by potassium ions and inhibited by KF, by the pyrophosphate analogs imidodiphosphate and aminomethylenediphosphonate (AMDP), and by the thiol reagent p-hydroxymercuribenzoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
137
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 50 publications
15
137
0
Order By: Relevance
“…The linear epitope-tagging cassette was transfected into PCF and BSF trypanosomes, where it integrated into the original TbVtc4 locus via homologous recombination. TbVtc4 co-localized with the vacuolar proton pyrophosphatase (TbVP1), an acidocalcisomal marker (31,40), in both PCF (Fig. 1B) and BSF trypanosomes (Fig.…”
Section: Tbvtc4mentioning
confidence: 99%
“…The linear epitope-tagging cassette was transfected into PCF and BSF trypanosomes, where it integrated into the original TbVtc4 locus via homologous recombination. TbVtc4 co-localized with the vacuolar proton pyrophosphatase (TbVP1), an acidocalcisomal marker (31,40), in both PCF (Fig. 1B) and BSF trypanosomes (Fig.…”
Section: Tbvtc4mentioning
confidence: 99%
“…Kinetic studies have shown that acidocalcisomes maintain a low internal pH due to the presence of a V-H + -ATPase [22][23][24] and a V-H + -PPase [8,11,13,15,[25][26][27] which pump H + into the lumen of the organelle. They also posses a Ca 2+ -H + translocating ATPase, a Ca 2+ -H + exchanger and a Na + -H + exchanger which permit a complex regulation of these ions by the cell It was proposed that acidocalsisomes are involved in mechanisms of Ca 2+ signaling, osmoregulation, pH homeostasis and energy storage [16,28].…”
Section: Introductionmentioning
confidence: 99%
“…Immunochemical approaches have detected some enzymes that could be responsible for these transport activities: a vacuolar H + ATPase ), a Ca 2+ -H + translocating ATPase and a vacuolar-type H + -pyrophosphatase. This last enzyme was considered similar to plant pyrophosphatases, as its activity was stimulated by K + and inhibited by Na + , Luo et al 1999, Rodrigues et al 1999a, 1999b, 2000.…”
Section: Isolation Of the Acidocalcisomementioning
confidence: 99%
“…Docampo and Moreno have recently (1999) suggested some possibilities, such as a storage role in calcium homeostasis and in energy metabolism, in view of the large accumulation of inorganic pyrophosphate (Urbina et al 1999) Other possibilities include pH control and osmoregulation, and the presence of Na + -H + exchange activity (Rodrigues et al 1999b).…”
Section: Isolation Of the Acidocalcisomementioning
confidence: 99%
See 1 more Smart Citation